HYDRAULIC FRACTURING ANALYSIS ON CONCRETE SAMPLE WITH BIAXIAL LOADING IN LABORATORY - IBNU RUSYD, ANDI (NIM : 121 04 092); Pembimbing : Dr. Nuhindro Priagung Widodo .,ST.,MT., MUH.
Hydraulic fracturing is one of the in situ stress measurement method to determine in situ stress state at a location that has great depth. This test method is to create a fissure in the wall of the drill hole by putting emphasis on a particular column of the drill hole with hydraulic fluid. In this study, hydraulic fracturing test will be tested to two concrete blocks of dimension 57 cm x 60 cm x 184 cm with a ratio of 1:10 and 1:20 with a horizontal hole at the centre of each concretes that are assumed to be the drillhole. By providing the biaxial loading the concrete blocks will form the maximum principal stress and minimum principal stresses. The amount given for loading 15 kN and 5 kN or for 0.09 MPa and 0.03 MPa. From the results obtained by testing a hydraulic fault breakdown value of pressure (Pb) for concrete 1: 10 for a rate of 1.02 MPa pressure of 0.0053 MPa / sec. For concrete 1: 20 obtained the value of breakdown pressure (Pb) of 1.27 MPa at a rate of 0.0075 MPa pressure / sec. The direction of the crack is generated in the direction of maximum horizontal stress (σH) and perpendicular to the minimum horizontal stress (σh). Tensile strength obtained from test hydraulic fracture has significant differences with the tensile strength obtained from direct tensile strength testing and test indirect tensile strength (Brazillian).